Español - Salas Ocampo, Luis Diego (2019)
This article determines the potentialities of the approach to children’s rights from a human rights perspective for the formulation of international cooperation projects. Thanks to the National System for the Protection of Children in Costa Rica, in the legal sphere, there are mechanisms to facilitate the participation of this sector in the generation of that kind of proposal. In university classrooms, there is a need to work on processes of project formulation, incorporating techniques, strategies, and methodologies that allow the specialist to be closer to the population under study. The objective is to guarantee the success and commitment of the planned initiatives. In Costa Rica, there is a strong commitment to this social area despite the development of an entire National System for the Protection of Children, which still has many historical debts with the sector, particularly with groups such as early childhood and adolescence.